An Overview of How HNCs Radiotherapy Affects Oral Microbiota: Shifts, Complications, and Management Strategies: Radiotherapy affects and oral microbiota - Ayoubi, Saman; Rahmanian, Mohammad; Hakimiha, Neda; Rezaei Tavirani, Mostafa; Jahani sherafat, Somayeh (Journal of Lasers in Medical Sciences, 2026)
Introduction: Radiotherapy (RT) is a primary treatment for head and neck cancers (HNCs). However, it can lead to acute and chronic side effects that diminish patients’ quality of life. RT-induced radiation can damage tissues and alter the oral microbiota. Multiple studies indicate that the oral microbiota significantly influences the development of these complications. Methods: This research aims to examine how radiotherapy affects the oral microbiota thoroughly, explore the link between these changes and clinical issues, and evaluate strategies for prevention and management. Results: RT damages salivary glands and the oral mucosa, leading to xerostomia (dry mouth) and oral mucositis. These physical and chemical changes alter the oral environment, resulting in dysbiosis. This dysbiosis is characterized by reduced microbial diversity and an increase in pathogenic species, including cariogenic bacteria like Streptococcus mutans and Lactobacillus, as well as inflammatory bacteria such as Prevotella, Fusobacterium, and Candida albicans. The review suggests that this dysbiotic profile may significantly contribute to the worsening of oral mucositis (through inflammatory and LPS-dependent pathways), promote radiation-induced caries (due to increased xerostomia and acidogenic bacteria), elevate the risk of oropharyngeal candidiasis, and play a role in osteoradionecrosis development. Conclusion: The findings indicate that the oral microbiota is not just a secondary factor in RT-induced damage but plays an active role in worsening RT-related side effects. Gaining a precise understanding of the oral microbiota as a potential therapeutic target is crucial, and incorporating oral microbiology into oncology protocols can greatly enhance patients’ quality of life and pave the way for new approaches in cancer supportive care.